2022
DOI: 10.1029/2021jc017714
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Physical and Biological Patterns Along the Tropical and South Atlantic Western Boundary: A Satellite Perspective

Abstract: We investigate the spatial and temporal patterns of satellite‐derived sea surface temperature, salinity and chlorophyll‐a concentration along the eastern South American coast. Two decade‐long time series (2002–2019; except for the salinity) allowed us to investigate changes from seasonal to interannual time scales on an array that stretches from the south (42°S) to the north (10°N) of the continent and from isobaths ranging from −50 to −1000 m away from the coast. The novelty of our approach is to assess compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Pacheco et al. (2022) suggested that the change in the orientation of the Brazilian coastline at Cape Frio modifies the spectral composition of oceanographic properties, which show a cascade of energy toward higher frequencies, that is, mesoscale activity and eddy formation. Uchoa et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacheco et al. (2022) suggested that the change in the orientation of the Brazilian coastline at Cape Frio modifies the spectral composition of oceanographic properties, which show a cascade of energy toward higher frequencies, that is, mesoscale activity and eddy formation. Uchoa et al.…”
Section: Introductionmentioning
confidence: 99%
“…We will use "eddy" and "meander" interchangeably since a meander is just an eddy still connected to a geophysical jet, in this case, the Brazil Current, rather than an isolated ring. Pacheco et al (2022) suggested that the change in the orientation of the Brazilian coastline at Cape Frio modifies the spectral composition of oceanographic properties, which show a cascade of energy toward higher frequencies, that is, mesoscale activity and eddy formation. Uchoa et al (2023) also revealed high mesoscale activity downstream of Cape Frio and Cape São Tomé, suggesting the frequent formation of mesoscale eddies in the Brazil Current.…”
Section: Introductionmentioning
confidence: 99%
“…Between 20 and 40°S, the western South Atlantic shelf is influenced by seasonally reversing winds, strong western boundary currents interacting with outer shelf waters, and a significant discharge of freshwater from the RdlP and, to a lesser extent, the LdP (see Palma et al 2008, Matano et al 2010. The seasonal amplitude of SST is highest (> 7°C) in the outer RdlP (Rivas 2010), exceeds 6°C in the neighboring shelf, and decreases northward, reaching about 1.5°C near Cape Frío (23°S; Pacheco et al 2022). In contrast, sea surface salinity and chl a present the highest seasonal amplitudes (exceeding 3 and 8 mg m −3 , respectively) over the southern Brazil continental shelf, south of Cape Santa Marta Grande , Pacheco et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal amplitude of SST is highest (> 7°C) in the outer RdlP (Rivas 2010), exceeds 6°C in the neighboring shelf, and decreases northward, reaching about 1.5°C near Cape Frío (23°S; Pacheco et al 2022). In contrast, sea surface salinity and chl a present the highest seasonal amplitudes (exceeding 3 and 8 mg m −3 , respectively) over the southern Brazil continental shelf, south of Cape Santa Marta Grande , Pacheco et al 2022. While salinity changes >10 may be observed along the coast in the outer RdlP estuary, particularly along the coast of Uruguay (Guerrero et al 1997).…”
Section: Introductionmentioning
confidence: 99%